Role of the gidan-gaado in sustainable urbanization - Muhammad, Umar Faruq (2020)
The traditional Gidan-gaado has continued to be one of the most widespread residential building typologies, which has been accommodating extended family dwelling in the urban cores of Northern Nigerian towns and cities like Keffi. Major motivating factor for this research was that, despite its dominance, the traditional neighbourhoods of Gidaajen-gaado have remainedterritories of urban relegation. Although the neighborhoods lacked basic amenities and infrastructure, the occupants, nevertheless, have remained resolute in preserving their symbol of socio-cultural dignity. That is in line, not only with sustainable urban housing, but also with the concept of cultural sustainability. This research sets out to determine the significance of its sustained existence and dominance, and also the roles it plays in the process of sustainable urbanization. In order to change the status quo, important roles of the Gidan-gaado needed to be explored and brought to the fore. The exploration was conducted against the backdrop of its major characteristics as well as its relevance in urban affairs. The research therefore aimed at proving its significance within the context of sustainable urban housing in Northern Nigeria. Appropriate methodologies were adopted based on providing the best answers to the research questions, in order to attain the objectives. Focus group and interviews were used to acquire in-depth perceptions from sampled participants. Survey was used to capture participants’ perceptions for possible generalization of the research findings. One major finding of the research was that, role of traditional urban Gidan-gaado was very significant from historical and socio-cultural perspectives. Its significance from architectural perspective was spatial rather than physical. A key contribution of this research was the documentation of how Gidaajen-gaado significantly influence sustainable urbanization by virture of their traditional dispositions and cultural dimension. The documentation has comprehensively captured the essence behind continuous existence of Gidan-gaado, within the cultural dimension of sustainability.